Pendampingan Pengelolaan Risiko dan Pengendalian Internal Kas pada UMKM Pempek Sayangan - Dhea Imroatul Fatihah; Devi Astriani; Trias Arimurti; Nur Azizah (Jurnal Pengabdian Masyarakat, 2026)
To assist Pempek Sayangan SMEs in enhancing their skills and business sustainability, this community service activity provides direct support and guidance in risk management. To deliver this service, we conducted interviews and observations with the SMEs. The research identified six major risks, including raw material shortages, poor raw material quality, and fluctuations in raw material prices. With the help and guidance provided, Pempek SMEs were able to perform a comprehensive risk assessment, identify risk sources, evaluate risks, and find solutions to mitigate these risks. We hope that this process will help the SMEs achieve their goals by increasing their knowledge and readiness to manage daily operational hazards. By addressing these risks, Pempek Sayangan SMEs are better prepared to face challenges, improve operational efficiency, and sustain their business growth. This initiative highlights the importance of effective risk management in fostering the long-term success and resilience of small and medium enterprises, while also strengthening their competitiveness in an increasingly competitive market.